Brief report: Aging adult utilization of an mHealth intervention for problem drinking - Sedotto, Robyn N. M.; Edwards, Alexandra E.; Dulin, Patrick L.; King, Diane K. (Frontiers in Public Health, 2024)
Alcohol consumption among aging adults is a growing concern due to its potential to exacerbate age-related health conditions. Developing accessible interventions for this demographic is imperative. Mobile health (mHealth) interventions offer a promising avenue, but their effectiveness and engagement among aging adults remain uncertain. This study is a secondary analysis that aimed to compare the utilization and outcomes of an mHealth intervention between aging (50+) and younger adults in a clinical trial of an mHealth intervention (Step Away) for reduced drinking. At the three-month follow-up, both age groups exhibited significant reductions in alcohol consumption and increased readiness for change. Furthermore, aging adults utilized the mHealth intervention significantly more, expressed a higher likelihood of continued use, and rated the intervention higher on the System Usability Scale (SUS). These findings suggest that mHealth interventions for alcohol-related issues can be equally effective for aging adults and that they readily engage with such tools and find them acceptable. This study underscores the potential of mHealth interventions as a viable solution for addressing alcohol-related concerns among aging adults. Further research targeting mHealth interventions tailored specifically to this demographic is warranted. Clinical trial registration: https://clinicaltrials.gov/ct2/show/NCT04447794, Identifier [NCT04447794].